Islamic Religious Education: Foundation for Resistance Against Corruption - Fatmawati, Fatmawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Islamic religious education is pivotal in nurturing moral values and ethical principles, serving as a cornerstone in combating corruption within society. This study conducted a literature review to explore the significance of Islamic education in addressing corruption. The analysis revealed that Islamic teachings emphasize integrity, honesty, and accountability, guiding individuals towards righteousness and justice. Moreover, Islamic education instills social responsibility and accountability, promoting transparency crucial in curbing corruption. Additionally, Islamic education adopts a holistic approach to personal development, encouraging self-discipline and reflection. The findings from the literature suggest that Islamic education empowers individuals to resist corrupt temptations and pressures, fostering moral character and ethical conduct. Consequently, integrating Islamic principles into education systems and societal frameworks cultivates a culture of integrity and accountability, essential in combating corruption and fostering a just and ethical society.